2354. Performance of Novel Clinical Case Definitions for Respiratory Syncytial Virus Infections in Young Infants: A Latent Class Analysis - Lalani, Karim (Open Forum Infect Dis, 2018)
BACKGROUND: Respiratory syncytial virus (RSV) is a major cause of pediatric morbidity and mortality worldwide. Appropriate case definitions are needed to accurately assess disease burden and evaluate novel RSV therapeutics and vaccines. Limited data exist on performance of RSV case definitions among young infants or in high-resource settings. METHODS: We used data collected on infants <6 months of age tested for RSV as part of routine clinical care at Children’s Healthcare of Atlanta between January 2010 and December 2015. We evaluated sensitivity, specificity, positive (PPV), and negative predictive values (NPV) of clinical features, existing case definitions used by the World Health Organization (WHO), and alternative definitions we constructed using latent class analyses (LCA) to detect laboratory-confirmed RSV infection. RESULTS: Among 565 infants tested for RSV, 161 (28.5%) had laboratory-confirmed RSV infection. Among all case definitions evaluated, WHO-acute respiratory infection (ARI) (“cough or sore throat or shortness of breath or coryza, and a clinician’s judgment that illness is due to infection”) was the most sensitive [98.1%, 95% confidence interval (CI), 96.1–100.0, NPV 96.3%, 95% CI 92.2–100.0. The definition developed through LCA (cough and shortness of breath and coryza and wheeze and poor feeding and chest in-drawing) was the most specific (95.8%, 95% CI 93.8–97.8; PPV 51.4%, 95% CI 34.9–68.0). CONCLUSION: The WHO ARI definition was the most sensitive for detecting laboratory-confirmed RSV infections among infants aged <6 months. However, alternative case definitions can confer higher specificity. Appropriate case definitions will vary depending on the content and setting in which they are utilized. [Image: see text] DISCLOSURES: All authors: No reported disclosures.